2020
DOI: 10.1177/2397847320906491
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity ofLantana camaraextract oil on controlling maize grain weevils

Abstract: Postharvest losses are known to be one of the serious constraints upon food security among farmers poor resource in Africa. The use of botanical insecticide in pest management during storage against weevils is often encouraged because synthetic insecticides produce multiple side effects on human and environment. In this study, the insecticidal property of methanol, ethanol, and ethyl acetate extracts of Lantana camara leaf oil and powder for controlling maize weevils, Sitophilus zeamais, was studied. Gas chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…The powdered leaves of Spear grass (I. cylindrica) could serve as a safer alternative to synthetic insecticides for the maize weevil (S. zeamais) infestation in stored maize grains (Ehisianya et al 2019). Extracts from L. camara leaf were used for the stored maize protection against the infestation of S. zeamais (Ayalew 2020). Recently, Loko et al (Loko et al 2021) showed the good potential of C. citratus as both antifeedant and fumigant toxic agent against Dinoderus porcellus Lesne.…”
Section: Chemical Composition Of the Oilsmentioning
confidence: 99%
“…The powdered leaves of Spear grass (I. cylindrica) could serve as a safer alternative to synthetic insecticides for the maize weevil (S. zeamais) infestation in stored maize grains (Ehisianya et al 2019). Extracts from L. camara leaf were used for the stored maize protection against the infestation of S. zeamais (Ayalew 2020). Recently, Loko et al (Loko et al 2021) showed the good potential of C. citratus as both antifeedant and fumigant toxic agent against Dinoderus porcellus Lesne.…”
Section: Chemical Composition Of the Oilsmentioning
confidence: 99%
“…Each essential oil and Talisma solution and the control were made in six replicates. After 24 hours, the number of dead weevils was counted and the weevil's mortality was calculated according to the following equation [81].…”
Section: Insecticidal Contact Toxicitymentioning
confidence: 99%
“…This test was used for each concentration, and the whole treatment was completed in triplicates. The repellent percentage (Pr) was calculated as follows [81].…”
Section: Repulsive Testmentioning
confidence: 99%
“…The toxic effect of L. camara was previously reported on tobacco caterpillar Spodoptera litura (Deshmukhe et al 2011), stored grain pests (Rajashekar et al 2014) cabbage white butterfly, Pieris brassicae (Sharma and Gupta 2009), and the rice moth, Corcyra cephalonica. Ayalew (2020) reported that stored maize could be protected from the infestation of S. zeamais by using extracts and oils of L. camara leaf and the author suggested that this repellent and mortality effect for insects could be because of the presence of bioactive compounds like 1-Eicosano, Paromomycin, Phytol, Pyrroline and Pyrrolizin. Alvi et al (2018) reported the toxic effect of R. stricta extract in controlling insect pests like Rhyzopertha dominica and Trogoderma granarium.…”
Section: Discussionmentioning
confidence: 99%